CRYSTALLINE STRUCTURE, MAGNETIC PROPERTIES, AND DEMAGNETIZATION FIELD ON NON-STOICHIOMETRIC Co2MnGa HEUSLER ALLOYS - Yan Pandu Akbar (NIM: 10213027), Mochammad
Heusler alloys (HA) are group of compound which exhibit a large variety of physical properties so that these materials have wide range potential applications. This final project will study systematically the effect of excess Co and Mn in Co2MnGa full-HA. Co2MnGa HA has several phase structure that depend on the occupancy of the elements in lattice position. This compounds exhibit magnetic behavior in temperature below 694 K with saturation magnetization about 4.14 μB/f.u in low temperature measurement. The elemental composition measurement using Inductively Coupled Plasma-Emission Optical Spectroscopy from samples with different Co and Mn concentration reveal the difference of composition compare to the starting composition. The X-Ray Diffraction measurement on grinded-single-crystalline powder show the formation of A2-type structure. The transformation into L21 type structure can be obtained by annealing the powder on 650 C for 10 hours. Beside the L21 type transformation, the formation of impurity phase from β-Mn also observed on all samples. Refinement of XRD from annealed-powder pattern reveal the substitution of atomic position which lead to variation of lattice constant and volume of studied-samples. The increasing of lattice constant and volume can be attributed to increasing of Mn concentration. The isothermal magnetization measurement on 2 K and 300 K using SQUID magnetometer show the deviation from Slater-Pauling rule. That deviation can be attributed to variation of atomic interaction strength induced by volume changing. This final project also calculate the mean of demagnetization field from several geometry variation of rectangular prism. The calculation will be used to correct the influence of external magnetic field on sample.